Nutrigenomics: A Narrative Review of Diet's Influence on Periodontal Health - Ashneet Kaur; Anchal Sood; Swantika Chaudhry; Aditya Khichy; Rachita Arora (Oral Sphere Journal of Dental and Health Sciences, 2025)
Nutrigenomics is a methodical study of the impact of nutrition input on the natural environment and genetic factors and their application to the health of the periodontium will offer valuable insights in the pathogenic processes of the disease. The relevance of the interface between nutrigenomics and prophylaxis/therapeutic approaches to periodontal disease is currently interrogated in the present review with respect to the relationship between periodontal status and the variety of nutrients and dietary compounds, the macronutrients, antioxidants, phytochemicals, and micronutrients. A review is also given on recent nutrigenomic discoveries that refer to gingival health. All of this evidence represents that genetic heterogeneity adjusts digestive efficiency and predisposition to periodontal pathology. The connection between nutrition and periodontal health is mused upon, and special consideration has been given to the effect that components of the diet have on the periodontal gene expression and inflammatory reactions. Despite the significant efforts undertaken, it is difficult to apply the nutrigenomic strategies in the practice of clinical work. Therefore, it is crucial that further research of the mechanisms peculiar to periodontal disease is continued to provide specific recommendations regarding diets, depending on the individual phenotype. In this way, this review underlines the promise of nutrigenomic technologies in supporting the field of periodontal care as well as in optimising the oral health of clinically heterogeneous populations.